Effects of manganese oxide nanoparticles embedment on optic-magnetic features of magnesium borotellurite doped europium glass - Siti Maisarah Aziz, 1991- , author; Md. Rahim Sahar, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Ph.D (Fizik)) - Universiti Teknologi Malaysia, 2018